Building Women's Self Reliance through Bouquet Based Creative Economy: A Participatory Action Research in Kadur Pamekasan - Nurul Ismaiyah; Nurul Azizah; Khoirun Nisa; Iftitah Dian Humairoh; Musayyadah Musayyadah (Khidmatuna : Jurnal Pengabdian Masyarakat, 2026)
Women in Kadur Village, Pamekasan, depend on agricultural and tobacco industry sectors that are highly susceptible to economic changes, with 78% earning monthly incomes below one million rupiah. This research aims to empower women through bouquet arrangement training to build independence and creative economy. This qualitative research employs a Participatory Action Research (PAR) approach that involves the community as active subjects in the research and empowerment process. Forty-five PKK members aged 18-55 years were purposively selected based on criteria of willingness to participate and commitment to follow the entire series of activities through consent agreements in Google Forms. The program was implemented in July 2025 through three PAR cycles: participatory planning through focus group discussions and community needs mapping, activity implementation in the form of intensive training covering arrangement techniques and basic entrepreneurship, and participatory reflection and evaluation to examine the impact of the empowerment program on women in Kadur Village. Data were collected through participant observation, in-depth interviews, focus group discussions, and documentation of the empowerment process. Data analysis used thematic analysis techniques to identify patterns of change in participants’ skills, attitudes, and economic behavior. The research results show that 82% of participants were able to create market-quality bouquets, a mindset shift from passive workers to active entrepreneurs in 56% of participants, and 7 participants successfully received bouquet service orders within 2 weeks post-training. The PAR program proved effective in facilitating active community participation in identifying problems, designing solutions, and implementing sustainable socio-economic changes.